Highly-stable, green-solvent-processable organic thin-film transistors: angular- vs. linear-shaped carbazoledioxazine derivatives. Issue 22 (23rd May 2018) - Wang, Yang; Tatsumi, Hiroki; Otsuka, Rikuo; Mori, Takehiko; Michinobu, Tsuyoshi
Abstract : Linear-shaped carbazoledioxazines can be processed from green solvents and exhibit a two orders of magnitude higher mobility than their angular-counterpart. Abstract : The design and synthesis of new dye/pigment-based semiconductors have made a significant contribution to the development of organic electronics. However, there are few detailed studies on the comparison of isomeric dye/pigment molecules, which play an important role in revealing the molecular structure–property–device performance relationships. In this study, we, for the first time, compared the thermal stability, optical, electrochemical, molecular assembling and charge transport properties of isomeric angular and linear-shaped carbazoledioxazine derivatives, namelyAng-CZ andLin-CZ, respectively. While the molecular shapes hardly affect the optical bandgaps and energy levels, they dramatically alter the charge transport characteristics. Accordingly, Lin-CZ exhibited a two orders of magnitude higher mobility thanAng-CZ, evaluated by thin-film transistors (TFTs). Further studies suggested thatLin-CZ tends to adopt a denser molecular packing motif and a higher molecular orbital overlapping thanAng-CZ which is revealed by grazing-incidence wide-angle X-ray scattering (GIWAXS), atomic force microscopy (AFM), and density functional theory calculations (DFT). More importantly, Lin-CZ-T, a π-extended derivative ofLin-CZ, showed a relatively high and stable TFT mobility of over 0.1 cm 2 V −1 s −1, which was revealed by using an environmentally-benign solvent and a pre-aggregation method. Our findings will provide direction for developing more promising molecular semiconductors and organic TFT technology.